2019
DOI: 10.7150/jca.26482
|View full text |Cite
|
Sign up to set email alerts
|

P16 Methylation Leads to Paclitaxel Resistance of Advanced Non-Small Cell Lung Cancer

Abstract: Paclitaxel-based chemotherapy is widely used as the first-line treatment for non-small cell lung cancer (NSCLC). However, only 20%-40% of patients have shown sensitivity to paclitaxel. This study aimed to investigate whether P16 methylation could be used to predict paclitaxel chemosensitivity of NSCLC. Advanced NSCLC ( N =45) were obtained from patients who were enrolled in a phase-III randomized paclitaxel-based clinical trial. Genomic DNA samples were extracted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
0
10
1
Order By: Relevance
“…shorter treatment duration [12]. We recently reported that P16 methylation could increase the resistance of lung (and stomach) cancers to paclitaxel treatment in a clinical trial [41]. In contrast, here, we reveal that P16 methylation can increase the sensitivity of lung and stomach cancers to palbociclib.…”
Section: Discussioncontrasting
confidence: 67%
“…shorter treatment duration [12]. We recently reported that P16 methylation could increase the resistance of lung (and stomach) cancers to paclitaxel treatment in a clinical trial [41]. In contrast, here, we reveal that P16 methylation can increase the sensitivity of lung and stomach cancers to palbociclib.…”
Section: Discussioncontrasting
confidence: 67%
“…Lung cancer is one of the most common malignant tumours in the world, accounting for 18.2% of the world's malignant tumour mortality. 12 It has also become the leading cause of malignant tumour death among Chinese urban residents. So far, although patients can obtain a range of effective treatments, including surgical resection, chemotherapy, targeted drug therapy and other methods, the prognosis of patients with NSCLC is still poor, the report pointed out that its five-year survival rate is only 11–15%.…”
Section: Discussionmentioning
confidence: 99%
“…The genes CDH1, CDKN2Ap16, RASSF1A, TERT , and WT1 were selected based on their roles as biomarkers in NSCLC and their putative gender sensitivity based on the current literature and our own research findings (reviewed in [ 64 ]). Among the selected markers, RASSF1A [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ] and, to a lesser extent, CDKN2Ap16 [ 73 , 74 , 75 , 76 , 77 ] are already accepted as methylation markers. The applicability of CDH1 [ 78 , 79 , 80 , 81 , 82 , 83 ] and WT1 [ 45 , 61 , 84 , 85 ] is still under investigation but may have a broader impact on many cancer entities; their interdependence adds to this potential.…”
Section: Methodsmentioning
confidence: 99%